PROPOSING A MODEL FOR ENTREPRENEURSHIP DEVELOPMENT: THE ROLE OF ENTREPRENEURS’ CASH WAQF INTENTION - Musa, Sherifah Oshioke; Che Mohd Salleh, Marhanum (Journal of Islamic Monetary Economics and Finance, 2018)
This paper aims to propose a model of entrepreneurship development by focusing on the role of cash waqf intention as a mediator on the relationship of cash waqf awareness, religiosity, attitude towards act, subjective norms, perceived behavioral and entrepreneurship development. By enhancing the theory of planned behavior, a structured question was designed to survey 459 Nigerian entrepreneurs. SEM analysis was used to test the theoretical framework and to propose a model of entrepreneurship development in Nigeria by means of Waqf. Result shows that the most important variables to explain entrepreneurs’ cash waqf intention for business growth are cash waqf awareness and attitude towards cash waqf. It is argued in this research that the presence of high level of cash waqf awareness and the attitude towards cash waqf can play an important role in achieving business growth. The paper extends the applicability of the theory of planned behavior, cash waqf awareness and religiosity in investigating the effect of cash waqf intention for business development.